Contextualizing Colonial History: Designing a Booklet on Local Dutch Heritage as an Alternative Teaching Resource for Indonesian Secondary Education - Nova Cahyo; R Soeharso; Novel Anak Lyndon (Indonesian Journal of History Education, 2025)
This study developed a booklet on Dutch colonial heritage buildings in Cepu as an alternative teaching resource for historical research learning in Indonesian high schools. Using a Research and Development (R&D) approach, the study identified a lack of locally relevant teaching materials under the new Merdeka Curriculum. The booklet was designed to provide contextual examples of historical research using nearby heritage sites. Expert validation by material and media specialists yielded high feasibility scores (90.3% and 86%, respectively). Limited trials with 36 students showed positive reception, with an 83% approval rating indicating the booklet was engaging and effective. The study concludes that locally anchored, visually rich booklets can enhance historical literacy, support curriculum flexibility, and foster student connection to regional history. This contributes to discourse on Curriculum and Media Innovation for Historical Literacy, offering a replicable model for developing context-sensitive resources in post-colonial educational settings.